ACHONOROPLASTIC CAPRINE FOETAL MONSTROSITY WITH ANURY ATRESIA AND SCROTAL HERNIA - JANA, DEBASIS; JANA, MOUSUMI (The Indian Journal of Animal Reproduction, 2023)
Bull Dog foetal monster or achondroplesla along with sorotal hernia atresia anl and anury in Black Bengal goat is reported.